2007
DOI: 10.2340/00015555-0254
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis Fungoides in Childhood: Description and Study of Two Siblings

Abstract: Primary cutaneous T-cell lymphomas are exceedingly rare in children and adolescents. However, mycosis fungoides (MF) is the most frequent primary cutaneous lymphoma diagnosed in childhood. Two cases of MF in siblings (a 14-year-old boy and his 10-year-old sister) are reported. On the basis of clinical features (histopathological and immunophenotypical findings) a diagnosis of MF patch lesions was made in both siblings. Since recent data in the literature have underlined a high frequency of the HLA-DQB1*03 alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Familial aggregation and ethnical differences in incidence point to genetic factors in the susceptibility to MF/SS. 11,12 To the best of our knowledge, scientific literature lacks data about HLA polymorphisms in Turkish MF patients. In this study, we found that HLA-A31, HLA-B51 and HLA-DR3…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation and ethnical differences in incidence point to genetic factors in the susceptibility to MF/SS. 11,12 To the best of our knowledge, scientific literature lacks data about HLA polymorphisms in Turkish MF patients. In this study, we found that HLA-A31, HLA-B51 and HLA-DR3…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies that show a higher frequency of HLA-DRB1*11 and/or HLA-DQB1*03 in patients with hematologic malignancies [ 83 ], non-Hodgkin’s lymphoma, diffuse large B-cell lymphoma [ 84 ], mycosis fungoides (cutaneous T-cell non-Hodgkin’s lymphoma) [ 85 88 ], acute lymphoblastic leukemia [ 89 ], chronic lymphocytic leukemia [ 90 ], hairy cell leukemia (B-cell leukemia) [ 91 ], and HCV virus-associated lymphoma [ 92 ] compared to controls. These data indicate a probable genetic basis of the lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient’s uncle died at 43 years of age from acute lymphoblastic leukemia. The occurrence of more cases of hematologic malignancies in a family further suggest a genetic contribution to the pathogenesis [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purpuric variants, including a case of MF mimicking a pigmented purpuric dermatitis, have also been reported [34,35]. The occurrence of MF in family members (parent-child or siblings) has also been described; a disease susceptibility secondary to specific human leukocyte antigen (HLA) alleles has been proposed to explain this phenomenon [36][37][38][39]. In these instances, the age of onset is often in earlier adulthood than in sporadic cases, typically presenting in the fourth and fifth decade of life, though differences in clinical behavior have not been identified [37,38].…”
Section: Cutaneous T Cell Lymphoma and Mycosis Fungoidesmentioning
confidence: 99%
“…In these instances, the age of onset is often in earlier adulthood than in sporadic cases, typically presenting in the fourth and fifth decade of life, though differences in clinical behavior have not been identified [37,38]. However, it is notable that "familial MF" has also been reported in siblings during childhood, or affecting both adult parents and their young children, though this occurrence is quite rare [36,37,39].…”
Section: Cutaneous T Cell Lymphoma and Mycosis Fungoidesmentioning
confidence: 99%